2011
DOI: 10.1167/iovs.11-8152
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative and Inflammatory Pathway Components Linked to TNF-α/TNFR1 Signaling in the Glaucomatous Human Retina

Abstract: Findings of this study reveal a number of proteins upregulated in the glaucomatous human retina that exhibit many links to TNF-α/TNFR1 signaling. By highlighting various signaling molecules and regulators involved in cell death and immune response pathways and by correlating proteomic findings with epigenetic alterations, these findings provide a framework motivating further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
208
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(216 citation statements)
references
References 79 publications
7
208
1
Order By: Relevance
“…Increased levels of TNF-a have been found in the aqueous humor, retina, and optic nerve microglia and optic nerve astrocytes from glaucoma patients (Yan et al 2000;Neufeld 2000, 2001;Tezel et al 2001;Sawada et al 2010). Activation of the signaling pathway downstream from TNF-a in glaucomatous human retinas has also been reported (Yang et al 2011). Several ligands and receptors of the TNF family were overexpressed at early stages of DBA/2J glaucoma, although not as early as was observed for the Il1-related cytokines (Howell et al 2011a,b).…”
Section: Inflammatory Signaling Pathways In Glaucomamentioning
confidence: 89%
See 2 more Smart Citations
“…Increased levels of TNF-a have been found in the aqueous humor, retina, and optic nerve microglia and optic nerve astrocytes from glaucoma patients (Yan et al 2000;Neufeld 2000, 2001;Tezel et al 2001;Sawada et al 2010). Activation of the signaling pathway downstream from TNF-a in glaucomatous human retinas has also been reported (Yang et al 2011). Several ligands and receptors of the TNF family were overexpressed at early stages of DBA/2J glaucoma, although not as early as was observed for the Il1-related cytokines (Howell et al 2011a,b).…”
Section: Inflammatory Signaling Pathways In Glaucomamentioning
confidence: 89%
“…Several studies using transcriptional profiling have identified early up-regulation of genes associated with inflammatory pathways in the retina and ONH in experimental models of glaucoma (Ahmed et al 2004;Johnson et al 2007Johnson et al , 2011Yang et al 2007;Kompass et al 2008;Nikolskaya et al 2009;Panagis et al 2010;Howell et al 2011aHowell et al , 2012. Collectively, these studies showed an up-regulation of inflammatory inducers/sensors (PRRs, e.g., TLRs), transducers (e.g., Mapk, Trif, MyD88) and amplifiers (e.g., Il1, Il6, Tnf, Ccl2) in human glaucoma Yang et al 2011;Tezel et al 2012) and in early stages of experimental glaucoma (Howell et al 2011a;Johnson et al 2011). In our study using DBA/2J mice, an inherited model of glaucoma, we were able to define early molecular changes that occur before detectable loss of RGCs and axons (Howell et al 2011a).…”
Section: Inflammatory Signaling Pathways In Glaucomamentioning
confidence: 96%
See 1 more Smart Citation
“…2 Interaction among differentially modulated genes in the apoptosis biochemical pathway, using KEGG, after hgf-FNDF-LC 50 and SCFA-LC 50 treatments binding to its receptor Fas on the surface of CRC cells (Yang et al 2011). Some compounds, such as sodium butyrate, sensitize cancer cells (including HT-29) to p53-independent, Fas-mediated apoptosis (Bonnotte et al 1998;Yang et al 2012), suggesting this pathway as a mechanism for the treatments on the induction of extrinsic apoptosis by the treatments evaluated in this study.…”
Section: Transcriptional Regulation Of Cell Cycle-related Genesmentioning
confidence: 99%
“…Primary Open Angle Glaucoma (POAG) and Primary Angle Closure Glaucoma (PACG) are subdivisions of Primary glaucoma (Shields, 2005), with POAG being more common in most populations, (AAOGP, 2010). The mechanism is multi factorial and complex neurodegeneration results from interactions between genetic, epigenetic, aging-related and other factors (Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%